1995
DOI: 10.1007/bf03010701
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide does not increase vomiting in children after myringotomy

Abstract: The aim of this study was to establish whether nitrous oxide has a clinically important effect on postoperative vomiting in children after myringotomy. We studied 320 healthy children of ages 0. Vomiting after general anaesthesia in children is common and may result in considerable postoperative morbidity.This vomiting is of multifactorial aetiology of which nitrons oxide is a possible contributing factor. Nitrous oxide may induce vomiting by causing bowel distension, decreasing gastric motility, increasing mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…The incidence of POV in infancy is one quarter that in children 1-3 years of age which in turn is approximately one-half that in older children and adolescents. 3,4 This is similar to the data from Splinter et al 2 The explanation for the lower incidence of POV in infancy remains unclear. 3 However, what is clear is that the target age of children who develop POV is between 2 and 12 yr. POV also depends on the type of surgery; the incidence is greater after strabismus, tonsillectomy and adenoidectomy or orchidopexy surgery than it is after extremity or orthopaedic surgery.…”
Section: Editorialsupporting
confidence: 88%
“…The incidence of POV in infancy is one quarter that in children 1-3 years of age which in turn is approximately one-half that in older children and adolescents. 3,4 This is similar to the data from Splinter et al 2 The explanation for the lower incidence of POV in infancy remains unclear. 3 However, what is clear is that the target age of children who develop POV is between 2 and 12 yr. POV also depends on the type of surgery; the incidence is greater after strabismus, tonsillectomy and adenoidectomy or orchidopexy surgery than it is after extremity or orthopaedic surgery.…”
Section: Editorialsupporting
confidence: 88%
“…He found an increased rate of PONV with the use of N 2 O [72]. By contrast, Splinter et al demonstrated that N 2 O did not increase POV in children undergoing dental restoration [73] and myringotomy [74]. However, there have been no studies evaluating the effect of intraoperative use with N 2 O on POV in children undergoing tonsillectomy.…”
Section: Risk Factor For Pov After Pediatric Ton-sillectomymentioning
confidence: 92%
“…Eine Reihe kleinerer Studien [93,165,169,170] zeigte signifikant weniger PONV bei N 2 O-Verzicht; dagegen konnte in größeren Studien kein Unterschied nachgewiesen werden [39,108,144]. Die Interpretation der Studien wird zudem erschwert, da verschiedene Symptome (Übelkeit, Erbrechen, Würgen) gemessen wurden und nichtvergleichbare Patientenkollektive ausgewählt wurden.…”
Section: Lachgas Und "Postoperative Nausea and Vomiting"unclassified